Move to unlimited vacations or remain with defined vacation policy? - Osland, Asbjorn (London : SAGE Publications: SAGE Business Cases Originals, 2020)
This case examines the pros and cons of defined vacation policies versus unlimited vacations. The Metropolitan Daily planned to offer unlimited vacation for exempt employees. Employees sometimes did not like losing accrued vacation, which was a feature of the unlimited policy. Some also believed they might find it awkward to request vacation time from managers; they always had crucial work pending that could interfere with the proposed vacation. The case narrative describes how employees may respond to such a shift in vacation allotment.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vacations, Employee